Determinants of Air Logistics Service Quality and Their Implications for the Performance of Air Export Companies in Bali - Fitri, I Gusti Agung Candra Maha; Maniah, Maniah; Mulyati, Erna (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Globalization and international trade require fast and efficient logistics systems, with air logistics playing a strategic role in handling high-value and time-sensitive commodities. In Indonesia, particularly Bali as a major air export hub, heavy reliance on air transportation has not been matched by improvements in logistics service quality and efficiency, as reflected in high costs, regulatory complexity, limited facilities, and weak customer relationships. This study examines the effects of capabilities, operational performance, regulations, customer relationships, and costs on air logistics service quality and their implications for the performance of air export firms in Bali. A confirmatory quantitative approach using SEM-PLS was applied to data from 245 respondents. The findings show that these factors significantly influence air logistics service quality, which in turn positively affects firm performance and serves as a mediating variable. These results highlight the strategic importance of service quality in enhancing air export competitiveness.